Rethinking Estate and Gift Taxation - Gale, William G. (Book collections on Project MUSE., 2011)
Although estate and gift taxes raise a small fraction of federal revenues, they have become sources of increasing political controversy. This book is designed to inform the current policy debate and build a conceptual basis for future scholarship. The book contains eleven original studies of estate and gift taxes, along with discussants' comments. The essays provide background and historical information; analyze the optimal taxation of estates and gifts; examine the effects of the tax on charitable contributions, saving behavior, the distribution and level of wealth, tax avoidance and tax evas.